In vitro floral induction from thin longitudinal sections and micro-cuttings of juvenile cork oak material - Mulin, Manorama; Pais, M S S (Trees-Structure and Function, 2003)
In vitro flowers were obtained from thin longitudinal sections excised at the proximity of the apical region or nodal regions of the main stem and axillary shoots of in vitro Quercus suber stock shoots as well as from field-grown seedlings. In vitro floral induction was also achieved from nodal segments of 8- to 9-month-old seedlings or from micro-cuttings of embryonic main shoot and its axillary shoots of 2- month-old seedlings. The more juvenile the material the shorter the period required to achieve flowering. Under the described experimental conditions we have thus been able to induce the expression of neoteny in a woody, longcycle species such as cork oak.
Keywords: apical or nodal regions; floral induction; neoteny; nodal segments or micro-cuttings; thin longitudinal sections